Prepectoral breast reconstruction - Sung-Eun Kim (Yeungnam University Journal of Medicine, 2019)
Implant-based breast reconstruction is the most commonly used reconstruction technique after mastectomy. This is because skin-sparing mastectomy has become possible with advancements in oncology. In addition, the development of breast implants and the advent of acellular dermal matrices have reduced postoperative complications and resulted in superior cosmetic results. The most frequently performed surgical breast reconstruction procedure for the past 20 years was the insertion of an implant under the pectoralis major muscle by means of the dual plane approach. However, some patients suffered from pain and animation deformity caused by muscle manipulation. Recently, a prepectoral approach has been used to solve the above problems in select patients, and the results are similar to subpectoral results. However, this technique is not always chosen due to the number of considerations for successful surgery. In this article, we will discuss the emergence of prepectoral breast reconstruction, indications and contraindications, surgical procedures, and outcomes.